Clinical Experience with 5-Aminosalicylate Preparations in Inflammatory Bowel Disease - A Review - C.N. Williams (Canadian Journal of Gastroenterology)
The efficacy of 5-ASA tablets is around 65 co 70% in patients with active ulcerative colitis, whereas the efficacy of the rectal preparations approach 100% when the treatment is for active distal disease. When there is more extensive left sided colonic disease, the efficacy of 5-ASA rectal preparations is not as high, but it is still much improved over that seen with oral 5-ASA preparations. There is no data available for total colonic disease of either ulcerative colitis or Crohn's disease. There is no controlled maintenance data available for Crohn's disease using 5-ASA preparations and no controlled or comparison data available for rectal preparations in Crohn's disease. There are no controlled dose-response studies of 5-ASA in patients with Crohn's disease. Thus, the most "therapeutic" dose is not known. The author's anecdotal evidence reports char patients with Crohn's disease affecting the rectum or left colon respond poorly to 5-ASA enemas. However. with continued use of more than six weeks at least a 50 to 60% respone is seen. In contrast, virtually all patients with ulcerative proctitis respond by six weeks and all are controlled by 10 to 12 weeks. When oral 5-ASA is compared with conventional oral sulfasalazine therapy, the efficacy is comparable. However, with 5-ASA the incidence of side effects is considerably lower; the number of patients discontinuing therapy is less; patient compliance is better, especially for the long term; dosage increase following inadequate action is more readily possible; and bacterial activation of the drug given is not necessary.